Climate, dust, and fire across the Eocene-Oligocene transition, Patagonia - Selking, Peter A.; Stromberg, Caroline; Dunn, Regan; Khon, Matthew J.; Carlini, Alfredo Armando; Davies-Vollum, K. Siân; Madden, Richard H. (Geology)
The Eocene-Oligocene transition (EOT) is typically interpreted as a time of drastic global cooling and drying associated with massive growth of a glacial icecap in Antarctica and the shift to an "icehouse" climate. The effects of this transition on the terrestrial environments, floras, and faunas of the Southern Hemisphere, however, have been unclear. Here we document simultaneous changes in fire regime and plant community in Patagonia, Argentina. Decreases in the concentration of magnetite in loessites from the Eocene-Oligocene Vera Member of the Sarmiento Formation correlate with decreases in the fraction of burnt palm phytoliths as well as more consistently palm-dominated phytolith assemblages. Association of magnetite and burnt palm phytoliths suggests intense wildfires, which appear to have been suppressed for ~200 k.y. shortly after the EOT. The disappearance of fire-related characteristics near the EOT is possible if changes in regional wind patterns-consistent with observed changes in sediment particle sizes-caused changes in seasonal precipitation. These results imply a more important role for fire in structuring Eocene-Oligocene landscapes than previously thought. Fil: Selking, Peter A. University of Washington; Estados Unidos Fil: Stromberg, Caroline. University of Washington; Estados Unidos. Burke Museum of Natural History and Culture; Estados Unidos Fil: Dunn, Regan. University of Washington; Estados Unidos. Burke Museum of Natural History and Culture; Estados Unidos Fil: Khon, Matthew J. Boise State University; Estados Unidos Fil: Carlini, Alfredo Armando. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Davies-Vollum, K. Siân. Sheffield Hallam University; Estados Unidos Fil: Madden, Richard H. University of Chicago; Estados Unidos